3D woven composite design using a flattening simulation. (December 2016) - Morioka, Kotaro; Ohtake, Yutaka; Suzuki, Hiromasa; Nagai, Yukie; Hishida, Hiroyuki; Inagaki, Koichi; Nakamura, Takeshi; Watanabe, Fumiaki
Abstract: Fiber composite materials have unique, advantageous mechanical properties that have made them highly desirable in a range of industries. In particular, 3D woven-fiber composites are highly resistant to delamination compared with laminated 2D woven-fiber composites and have been adopted in various advanced products. This paper focuses on the design of 3D woven-fiber composite products and proposes a flattening simulation method for designed 3D models with constant thickness. The proposed method estimates the shape of a flat material and the fiber directions in the 3D model design; deformation phenomena of 3D woven-fiber materials are also considered in order to improve the accuracy of the proposed method. CT images are used to compare the simulation results with the actual deformation of 3D woven-fiber materials and confirm the ability of our method to effectively design the fiber direction base on the 3D model and to estimate the shape of flat materials. Highlights: Flattened shape of fiber material is obtained for given product design. Flattening simulation deal with the anisotropy and thickness of 3D woven fiber materials. Flatten shape is optimized for given fiber directions.